TINGKAT PENGETAHUAN PENGGUNAAN OBAT BENTUK SEDIAAN SUPPOSITORIA PADA MASYARAKAT DESA LANGKAP KECAMATAN BESUKI KABUPATEN SITUBONDO (Periode Februari 2021) - Zuanta Pangestuti (Akademi Farmasi Mitra Sehat Mandiri Sidoarjo, 2021)
Knowledge is information or information that is known or realized by someone. Community knowledge is the result of knowing and this occurs after people have sensed a certain object. The purpose of this study was to determine the level of knowledge of the use of suppository dosage forms in the community of Langkap Village, Besuki District, Situbondo Regency. This type of research is descriptive research with analytical observational method with the sampling technique used in this research is purposive sampling. The measuring instrument used in this study was a questionnaire distributed to 45 respondents with criteria for the age of 15-49 years. Based on the results of the research